Uma contribuição ao controle de motores de combustão interna de ignição por centelha na condição de marcha lenta - Gabriel Teixeira Braga (2007)
The present work is placed in the context of an open Electronic Control Unit (ECU) development, intended to supply the lack of a flexible control system that favors research development in the engine area. After the ECU's hardware architecture definition in a previous work, was defined as objective of the present work the development of a complete strategy of injection, ignition and speed control of an Internal Combustion Engine (ICE) in the idle condition. In this condition the engine is not accelerated, and in this way must be kept by ECU in the lesser possible speed to minimize consumption, but preserving engine's smooth functioning, despite of loads applied in its shaft. Although nonlinear and complex dynamics of the engine, the restriction of the operation to the idle condition made possible the adoption of classic control techniques, based in PI controllers in parallel with feed forward strategies for disturbances rejection and loop decoupling. Amongst the implemented strategies, the ignition control requires the information of knocking phenomenon occurrence, measured by an independent system developed in previous works, through the spectral analysis of the engine's structural vibration signal. In this way, a simplified communication protocol was also developed, based in CAN (Controller Area Network) interface, through which it was possible to change information between ECU and the knocking identification system. Results obtained with engine in a bench show that the developed strategies are capable to keep the correct functioning of the engine, with low level of emissions and consumption. Keywords: electronic engine management, idle speed control, automotive embedded systems.